Toward Single Atom Chains with Exfoliated Tellurium - Hugh O. H. Churchill; Gregory J. Salamo; Shui-Qing Yu; Takayuki Hironaka; Xian Hu; Jeb Stacy; Ishiang Shih (Nanoscale Research Letters, 2017)
Abstract We demonstrate that the atom chain structure of Te allows it to be exfoliated as ultra-thin flakes and nanowires. Atomic force microscopy of exfoliated Te shows that thicknesses of 1–2 nm and widths below 100 nm can be exfoliated with this method. The Raman modes of exfoliated Te match those of bulk Te, with a slight shift (4 cm−1) due to a hardening of the A1 and E modes. Polarized Raman spectroscopy is used to determine the crystal orientation of exfoliated Te flakes. These experiments establish exfoliation as a route to achieve nanoscale trigonal Te while also demonstrating the potential for fabrication of single atom chains of Te.